2008
DOI: 10.1136/jnnp.2007.119883
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in spinocerebellar ataxia type 6

Abstract: Our results demonstrate that specific cognitive deficits occur in patients with SCA6, independent of ataxic motor dysfunction. These deficits may reflect disruption of cortico-cerebellar circuits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
48
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 38 publications
(32 reference statements)
10
48
1
Order By: Relevance
“…Again, we think this unlikely, because the motor output in the behavior task was minimal, a single button press across a single joint. Table 3 The clusters activated by the contrast Hits>Early errors between the groups: control group and SCA group Cognitive and executive impairment are prominent in spinocerebellar patients with extracerebellar pathology (spinocerebellar ataxia 1, 2, and 3); however, mild cognitive and executive impairments were observed in both spinocerebellar ataxia 6 and 8-our sample- [60][61][62]. What is interesting is that more than other categories, these patients have trouble in theory of mind tasks, such as recognition and attribution of social and emotional responses [63].…”
Section: Discussionmentioning
confidence: 99%
“…Again, we think this unlikely, because the motor output in the behavior task was minimal, a single button press across a single joint. Table 3 The clusters activated by the contrast Hits>Early errors between the groups: control group and SCA group Cognitive and executive impairment are prominent in spinocerebellar patients with extracerebellar pathology (spinocerebellar ataxia 1, 2, and 3); however, mild cognitive and executive impairments were observed in both spinocerebellar ataxia 6 and 8-our sample- [60][61][62]. What is interesting is that more than other categories, these patients have trouble in theory of mind tasks, such as recognition and attribution of social and emotional responses [63].…”
Section: Discussionmentioning
confidence: 99%
“…Globas et al failed to provide clear evidence for cognitive deficits in SCA6 patients [11]. However, we recently revealed significant impaired visual memory and verbal fluency in genetically confirmed SCA6 patients [12], suggesting that SCA6 patients have prefrontal dysfunction. Previous studies have indicated hypoperfusion restricted to the cerebellum [10], however these results may be attributable to the small sample size of the SCA6 patients used.…”
Section: Introductionmentioning
confidence: 96%
“…(Table 1) Thirteen genetically confirmed SCA6 patients from thirteen families and 21 control subjects were enrolled in this study (Table 1). These 13 SCA6 patients were from the same pool of 18 patients who were examined in our previous report [12]. All were native Japanese speakers.…”
Section: Introductionmentioning
confidence: 99%
“…Globas et al [50] examined cognitive function in 12 patients with genetically confirmed SCA6, but found only mild deficits in fronto-executive tasks that were not significantly different from those in controls. However, Suenaga et al [51] examined cognitive function in 18 patients with genetically confirmed SCA 6, and showed that verbal fluency and immediate visual memory were markedly impaired. These cognitive dysfunctions did not correlate with CAG repeat length.…”
Section: Spinocerebellar Ataxia Typementioning
confidence: 99%